Yoga as a therapeutic approach to mental health in university students: a randomized controlled trial - Castellote-Caballero, Yolanda; Carcelén-Fraile, María del Carmen; Aibar-Almazán, Agustín; Rivas-Campo, Yulieth; González-Martín, Ana María (Frontiers in Public Health, 2024)
The purpose of this study has been to analyze the efficacy of a yoga-based intervention on stress, emotional well-being, state anxiety and trait anxiety in university students.This study was a randomized controlled trial. The sample consisted of 129 university students, of which 65 underwent a yoga training for 12 weeks and a control group that did not carry out any type of intervention. The primary outcome variable was stress, which was collected through The Perceived Stress Scale (PSS). The secondary outcomes were, emotional well-being which was measured through the Warwick-Edinburgh Mental Well-being Scale (WEMWBS), and anxiety through State-Trait Anxiety Inventory (STAI). All variables were measured before and after the intervention.Results: Participants in the experimental group showed statistically significant improvements in the primary outcome perceived stress (Cohen's d = 0.44)) and the secondary outcomes, emotional wellbeing (Cohen's d = 0.47), and both state anxiety (Cohen's d = 0.38) and trait anxiety (Cohen's d = 0.80) compared to the control group that did not carry out any type of physical training.This study demonstrated that a 12-week yoga intervention can significantly reduce perceived stress and anxiety, and improve emotional well-being in university students. Initially, the experimental group (EG) reported higher levels of stress and anxiety than the control group (CG), but after the intervention, the EG experienced significant improvements compared to the CG.